The Effect of Passing on Volleyball Games Using Basketball Media - Rifaldi, Rifaldi; Nur, suaib; Salama, Nurdin (Physical Education, Health and Recreation Study Program, Universitas Insan Budi Utomo, Indonesia, 2023)
The use of basketball media affects the passing of athletes with the results of the pre-test passing on volleyball athletes at the Muhammadiyah University of Palopo club is still lacking, the goal is that with basketball as a burden it will affect passing accuracy. Using the experimental method, pretest and posttest group, the total sample = 12 athletes. lasted for 2 months, 16 meetings were held with the first meeting taking pre-test data by passing over using a volleyball to the front across the net which had been given a number, at meeting 2 to meeting 15 given treatment or treatment of athletes using ball media basketball in various ways, passing over with athletes, passing over with walls and passing over putting the ball into the basketball net, at the 16th meeting taking the final post-test data by passing over using a volleyball forward with across the net the numbers that have been given every place. Using test with the results of the study that using basketball passing media for athletes has an effect, it can be concluded that there is an influence with the pre-test result = 9.25, which is low compared to the post-test result = 14.08. and tcount = 9.298 and ttable = 2.228 then ha will be accepted and ho will be rejected. So, top passing exercises using basketball media have a significant influence on the volleyball club of the Muhammadiyah University of Palopo.